Integration of Qur'anic Values in Tribrata and Catur Prasetya POLRI: Reconstruction of Institutional Ethics Based on Religious Moderation - Rahman, Gafil Bunayya; Hariyadi, Muhammad; Rezi, Muhamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This article aims to analyze the integration of Qur'anic values into the Tribrata and Catur Prasetya of the POLRI, and their relevance to strengthening institutional ethics and religious moderation in the development of police human resources. This study departs from the fact that research on religious moderation tends to develop in the context of policy, education, and the digital space, whereas studies on Tribrata and Catur Prasetya are more firmly placed within the framework of professional ethics and institutional professionalism. Using qualitative research based on literature reviews and thematic interpretation, this article examines Qur'anic verses related to wasathiyyah, amanah, al-'adl/qist, tasamuh, tawazun, and i'tidal, and then compares them with the formulations of Tribrata and Catur Prasetya as life and work guidelines for the POLRI. The results of the study show that the Qur'anic values correspond substantively with the ethos of devotion, justice, protection, service, and moral responsibility within the POLRI. Tribrata and Catur Prasetya, therefore, are not sufficiently understood as a formal ethical formulation of the organization, but can be reread as a Qur'anic institutional ethos that deepens the moral-spiritual basis of the apparatus's formation. This article emphasizes that integrating Qur'anic values into the POLRI's institutional ethics strengthens religious moderation that is more transcendental, humanist, and oriented towards public benefit.